النتـــــــــيـــــجـــــــــــة الـمـــــــــــــــــاديــــة وغيـــــــــــــــــر الـمـــــــــــــادية للجـــــــــــــــــــريـــــــمــــة (قراءة جديدة للنتيجة الإجرامية) : The material and non-material results of crime : A New Reading of the Criminal Result Dr. Abdulqader Qaid Saeed Al-Majeedi (The Scientific Journal of University of Saba Region, 2021)
اعتاد بعض فقهاء القانون الجنائي على تقسيم الجرائم, بالنظر إلى نتيجتها الإجرامية, إلى قسمين: جرائم مادية وجرائم شكلية، وتكون النتيجة الإجرامية في النوع الأول مادية، بينما تكون شكلية في النوع الثاني.  ثم عمد بعض شراح القانون الجنائي إلى تقسيم الجرائم إلى جرائم الضرر وجرائم الخطر، فعُدت الجرائم المادية من قبيل جرائم الضرر والجرائم الشكلية من قبيل جرائم الخطر، فكل جريمة تنتج نتيجة إجرامية؛ وتكون هذه النتيجة - في جميع أحوالها- نتيجة مادية، سواء وُصفت بنتيجة الضرر في جريمة القتل أو بنتيجة الخطر في جريمة إطلاق النار على المجني عليه ولم تصبه.   ولكشف الغموض عن النتيجة الإجرامية، أوردت تقسيماً جديداً لها، أرى أنه جديد باعتماده من قبل فقهاء القانون الجنائي، وهو أن النتيجة الإجرامية تنقسم إلى نتيجة مادية ونتيجة غير مادية أي أدبية، وحللت أقوال فقهاء القانون الجنائي بشأن النتيجة الإجرامية لبيان الوصف الدقيق لها.  وخلصتُ إلى أنه ينبغي تقسيم الجرائم - بالنظر للنتيجة الإجرامية- إلى قسمين:الأول: نتيجة إجرامية مادية، وذلك في أغلب الجرائم كالقتل والسرقةالثاني: نتيجة غير مادية، أي أدبية (معنوية أو نفسية)، جرائم القذف والسب والتهديد وما شابهها؛ تصيب نفسية المجني عليه. لهذا أوصي باستعمال مصطلح النتيجة الإجرامية المادية في مقابل النتيجة غير المادية أي الأدبية (النفسية أو المعنوية).وأوصي القاضي الجنائي في بلادي العربية بضرورة النظر إلى الآثار الأدبية للنتيجة الإجرامية، فالشرع والعقل يوصي بفعل ذلك، فالحكمة ضالة المؤمن أنى وجدها فهو أحق بها.AbstractSome criminal law scientists have divided crimes according to their criminal results into material crimes and formal crime. The result in the first type of crime is material and it is formal in the second type. However, crimes have been also divided by other scientists into crimes of harm and crimes of danger. Accordingly, material crimes are considered as crimes of injury whereas formal crimes are considered as crimes of danger. Each crime, however, lead to a criminal result. This result is invariably material whether it is described as a result of harm as in the case of a murder crime or as a result of danger in the case of a crime of shooting at the victim but not hitting him.To avoid such confusion, the researcher introduces a new classification of criminal results which, according to the researcher, should be approved by the jurists of criminal law. The new classification indicates that the criminal result is divided into material and non-material i.e. moral. In addition, the researcher analyzes the sayings (proclamations) of the criminal law jurists about the criminal result to provide a precise description for it.The study reached the result that crimes should be divided according to their results into:material criminal result as in the most of the crimes including murder and theft.non-material result (moral or psychological) as in the crimes of defamation, insult, threats etc. which affects the psychological state of the victim. Therefore, the researcher recommends that such classification should be used. The researcher also recommended that criminal judges in Arab countries to investigate the moral consequences of the criminal result.